The effect of doping of La3+ ions on multiferoic Bi2-xLaxFe4O9 (x = 0; 0.2; 0.5; 1.0) as microwave absorber - yohanes edi gunanto; Wisnu Ari Adi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2020)
The synthesis and characterization of Bi2-xLaxFe4O9 multiferoic material (x = 0; 0,2; 0,5; 1) have been used as microwave absorbers. Bi2-xLaxFe4O9 (x = 0; 0,2; 0.5; 1) material was made by solid state reaction with mechanical milling technique using high energy milling (HEM). X-ray diffraction (XRD) was used for characterization of formation phase and crystal structure, scanning electron microscopy-energy dispersive spectra (SEM-EDS) was used to characterize surface morphology and particle size, whereas vector network analysis (VNA) was used for characterization of absorption capability microwaves. The characterization results showed that all samples were in phase with orthorombic crystal structure, P bam space group. The average particle size was 578.5 nm with an almost homogeneous form. Meanwhile, the best sample in absorbing microwaves was obtained for x = 0.2 with reflection loss value (RL) around -21dB at 11.2 GHz frequency